2013
DOI: 10.4028/www.scientific.net/amr.765-767.3045
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Dynamic Programming in the System Optimization of Environmental Problem

Abstract: Based on the application in the system optimization of environmental problem, the solution procedures of dynamic programming are introduced. Combining with some typical problems, such as the shortest path problem, the optimum scheme problem of water treatment and the water resources allocation problem, reliability analyses of the solution procedures by LINGO software is processed. The results show that the LINGO software can effectively solve this kind of dynamic programming problem and is the effective tool t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…It was found that by changing the current loader-to-truck allocation strategy, average truck cycle time and loaders driving distance can be significantly reduced by 14.6% and 18.4% respectively. Zhao J. Liu B. Wei F. (2013) [6] explained environmental problem. This is one of the biggest issues faced by mankind.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that by changing the current loader-to-truck allocation strategy, average truck cycle time and loaders driving distance can be significantly reduced by 14.6% and 18.4% respectively. Zhao J. Liu B. Wei F. (2013) [6] explained environmental problem. This is one of the biggest issues faced by mankind.…”
Section: Introductionmentioning
confidence: 99%